Peran Pembelajaran Pendidikan Agama Islam dalam Membentuk Karakter Peserta Didik di Sekolah Menengah Kejuruan Negeri 1 Tembilahan Hulu - Zulkifli Zulkifli; Hasniwati Hasniwati (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2020)
Islamic religious education is closely related to character. education has become a hot discourse in the world of education in Indonesia, but the emergence of the idea of ​​"character education is interrupting our nation, especially when it is hitting the nation. The problems that occur such as violence, corruption, manipulation, lying practices in the world of education ranging from cheating on exams, lack of exemplary among national leaders, and so on, actually concern character issues. Character education in schools must be carried out because there are still many of our generations of students who are sitting in school and need character education so that in the future they become people who are not only intellectually intelligent and skilled in the field of skills but also have character. The world of education is expected to be the driving force for Character Development and Education to be a necessity because education does not only make students smart. Education is also to build character and manners in everyday life. In addition, character planting through methods: teaching, exemplary, priority.